Synthesis, Characterization, and Photocatalysis of Fe-Doped : A Combined Experimental and Theoretical Study - Liping Wen; Baoshun Liu; Xiujian Zhao; Kazuya Nakata; Taketoshi Murakami; Akira Fujishima (International Journal of Photoenergy)
Fe-doped TiO2 was prepared by hydrothermal treating Ti peroxide sol with different amount of iron nitrate. Fe ions can enter TiO2 lattice by substituting Ti4+ ions, which significantly affect the crystallinity and morphology of TiO2 nanoparticles. Fe doping also influences the UV-Vis absorption and photoluminescence of TiO2, due to the change of electronic structure. It is shown that Fe ions are more easily doped on TiO2 surface than in bulk. The theoretical computation based on the density functional theory (DFT) shows that the Fe ions in TiO2 bulk are localized and mainly act as the recombination centers of photoinduced electrons and holes. Some results support that the Fe3+ ions on surface can form intermediate interfacial transfer pathway for electrons and holes, which is beneficial for increasing the photocatalytic activity of TiO2. The photocatalytic activity first increases and then decreases as the Fe concentration increases, which is coaffected by the bulk-doped and surface-doped Fe ions.